The Impact of Diabetes on Cognitive Performance: A Comprehensive Review - Zhou, Xudong (International Journal of Public Health and Medical Research, 2025)
Diabetes Mellitus, a prevalent metabolic disorder, is increasingly acknowledged as a critical determinant of cognitive impairment. This comprehensive review synthesizes the current understanding of the pathophysiological mechanisms underlying cognitive deficits in diabetic individuals. It explores the contributions of chronic hyperglycemia, microvascular pathology, impaired insulin signaling, oxidative stress, and neuroinflammation as key drivers of neuronal injury and cognitive decline. And then the review delineates a range of risk factors—including advanced age, inadequate glycemic control, hypertension, and dyslipidemia—that exacerbate susceptibility to cognitive dysfunction in this patient population. The utility of advanced neuroimaging techniques and neuropsychological assessments in the detection and monitoring of cognitive changes is rigorously evaluated. Additionally, the article examines emerging preventive and therapeutic strategies, such as rigorous blood glucose control, management of cardiovascular risk factors, administration of antioxidants and anti-inflammatory agents, neuroprotective interventions, and psychological support. The review concludes with a discussion of its clinical relevance, underscoring the necessity for timely diagnosis and integrated management approaches to mitigate the cognitive burden of diabetes, and suggests avenues for future research aimed at addressing current knowledge voids and improving patient outcomes.